Doctrine of Eternal Recurrence--The U.S. Military and Counterinsurgency Doctrine, 1960-1970 and 2003-2006 RAND Counterinsurgency Study--Paper 6 - Long, Austin (RAND Corporation, 2008)
By comparing modern counterinsurgency doctrine and operations to those of 1960s, this paper tests and ultimately disproves the assumption that doctrine as written and operations as conducted are tightly linked. Ingrained organizational concepts and beliefs have a much greater influence on operations than written doctrine, and altering these beliefs will require the U.S. military to reorient itself mentally as well as physically.